2017
DOI: 10.21608/scuj.2017.6653
|View full text |Cite
|
Sign up to set email alerts
|

Mango, Orange and Mandarin Peels Oleoresins to Prepare Natural and Healthy Instant Flavor Drinks

Abstract: Mango and citrus are major processed fruits in Egypt that results in large quantities of wastes and byproducts rich in various bioactive components such as water soluble and insoluble antioxidants and essential oils. Therefore, the objective of this study was to produce instant flavor drinks from oleoresins which obtained from fruit industry wastes (mango, orange and mandarin peels). Fruit peels are natural sources for dietary antioxidants and flavor. Mango, orange and mandarin peels industrial by-products con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The present data were confirmed by the results of Masoud and El-Hadidy [44] who found that total phenols of mandarin was (50.51±2.41mg/g GAE) and total flavonoids was (1.65±0.02 mg/g RE). Ghasemi et al reported that total phenolic contents of Citrus reticulate varieties peel powder was in the range of 104.2 to 172.1 mg/ g as GAE [45].…”
Section: Hua Et Al (supporting
confidence: 91%
“…The present data were confirmed by the results of Masoud and El-Hadidy [44] who found that total phenols of mandarin was (50.51±2.41mg/g GAE) and total flavonoids was (1.65±0.02 mg/g RE). Ghasemi et al reported that total phenolic contents of Citrus reticulate varieties peel powder was in the range of 104.2 to 172.1 mg/ g as GAE [45].…”
Section: Hua Et Al (supporting
confidence: 91%
“…While, vitamin C as control 100 ppm 97.1%, 50 ppm 96.81%, and 25 ppm 97.01%. Orange peels oleoresin has antioxidant activity from 54.20% to 73.0%13 . D.…”
mentioning
confidence: 99%